Data Integration in the Life Sciences 8th International Conference, DILS 2012, College Park, MD, USA, June 28-29, 2012. Proceedings - Bodenreider, Olivier; Rance, Bastien; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg, 2012)
This book constitutes the refereed proceedings of the 8th International Conference on Data Integration in the Life Sciences, DILS 2012, held in College Park, MD, USA, on June 28-29, 2012. The 11 revised papers included in this volume were carefully reviewed and selected. The papers cover the following topics: foundations of data integration, new paradigms for data integration, and integrating clinical data.
Keywords: Computer science; Database management; Data mining; Information storage and retrieval systems; Artificial intelligence; Computer Science; Information Systems Applications (incl. Internet).; Artificial Intelligence (incl. Robotics).; Information Storage and Retrieval; Database Management; Data Mining and Knowledge Discovery